Thermophoretic tweezers for single nanoparticle manipulation - Stergar, Jošt; Osterman, Natan (Beilstein Journal of Nanotechnology, 2020)
We present the trapping and manipulation of a single nano-object in an aqueous medium by optically induced temporally varying temperature gradients. By real-time object tracking and control of the position of the heating laser focus, we can precisely employ thermophoretic drift to oppose the random diffusive motion. As a result, a nano-object is confined in a micrometer-sized trap. Numerical modeling gives a quantitative prediction of the effect. Traps can be dynamically created and relocated, which we demonstrate by the controlled independent manipulation of two nanoparticles.
Keywords: laser; microfluidics; nano-manipulation; thermophoresis; trapping; tweezers